2022
DOI: 10.1017/s1460396922000255
|View full text |Cite
|
Sign up to set email alerts
|

Systematic self-reporting of patients’ symptoms: improving oncologic care and patients’ satisfaction

Abstract: Background: In recent years, there has been a growing interest to enhance patients’ symptom management during routine cancer care using patient-reported outcome measures. The goal of this study is to analyse patients’ responses to the Edmonton Symptom Assessment System (ESAS) to determine whether patient-reported outcomes could help characterise those patients with the highest supportive care needs and symptom burden in order to help provide targeted support for patients. Methods: In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…These observations are consistent with similar studies that have been reported in the literature. 9,44,6264 Yennurajalingam et al 44 used the ESAS patient-reported outcome questionnaire to investigate factors associated with a feeling of wellbeing among 826 advanced lung or non-colonic gastrointestinal cancer patients and observed that patient-reported wellbeing was significantly associated with tiredness. Wilding et al 63 also investigated the associations between cancer-related symptoms, health-related quality of life and poor psychological outcomes in 13,097 prostate cancer patients treated with androgen deprivation therapy (ADT) and reported that clinically significant tiredness was strongly associated with poor wellbeing in patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These observations are consistent with similar studies that have been reported in the literature. 9,44,6264 Yennurajalingam et al 44 used the ESAS patient-reported outcome questionnaire to investigate factors associated with a feeling of wellbeing among 826 advanced lung or non-colonic gastrointestinal cancer patients and observed that patient-reported wellbeing was significantly associated with tiredness. Wilding et al 63 also investigated the associations between cancer-related symptoms, health-related quality of life and poor psychological outcomes in 13,097 prostate cancer patients treated with androgen deprivation therapy (ADT) and reported that clinically significant tiredness was strongly associated with poor wellbeing in patients.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with other similar studies that have been reported in the literature. 9,23,44,45,6264…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations